Hydrodynamic characteristics of deep-water bridge floating foundations with different mooring systems. (1st August 2022) - Xiang, Sheng; Cheng, Bin; Tang, Miao; Zhang, Songyan
Abstract: This paper focuses on the hydrodynamic characteristics of the floating foundations which are used to support the deep-water floating bridges. A model test is conducted for the bridge floating foundation considering three typical mooring systems, namely Incline Cables only (IC), Tension Legs only (TL), and Incline Cables & Tension Legs (IC&TL), for comparison. Based on statistical and spectral analyses, the hydrodynamic characteristics of floating foundations under wave and current, regarding platform motions and mooring tensions, are investigated. In IC system, the platform heave and roll motions are excited by waves with relatively wide range of frequencies, and a coupling effect between sway and roll is recognized. In TL system, remarkable resonance in sway motion is observed under irregular wave loading, while other responses are well suppressed. The responses of IC&TL system are generally dominated by platform sway resonance, and superior performance with respect to both static and dynamic behaviors is shown in this system. The floating foundation systems would behave statically under the current only condition, while for conditions combining wave and current, the superposed current would mitigate the horizontally dynamic responses, and enhance the vertically heave oscillations of the systems. Highlights: A hydrodynamic model test considering wave and current loadings was conducted for bridge floating foundations. Bridge floating foundations with three typical mooring systems were considered in model test for comparison. Structural hydrodynamic responses including floating platform motion and mooring forces were finely measured. Hydrodynamic characteristics of bridge floating foundations have been investigated by statistical and spectral analyses. Effects of environmental wave and current on the dynamic responses of floating foundations have been revealed.